Natural course of Fabry disease with the p Arg227Ter (pR227*) mutation in Finland: Fast study - Pietilä-Effati P; Saarinen JT; Löyttyniemi E; Autio R; Saarenhovi M; Haanpää MK; Kantola I (My University, 2025)
Background
Fabry disease is caused by a deficient or an absent alfa‐galactosidase A activity and is an X‐linked disorder that results in organ damage and a shortened life span, especially in males. The severity of the disease depends on the type of mutation, gender, skewed X‐chromosome inactivation, and other still unknown factors.
Methods
In this article, we describe the natural course of a common classic Fabry disease mutation, p.Arg227Ter or p.R227*, in Finland.
Results
Four males and ten females belonged to two extended families. The mean age was 46 years (SD 18.4). Six patients (43%) had cardiac hypertrophy, three patients (21%) had ischemic stroke, and none had severe kidney dysfunction. Three patients had atrial fibrillation; two patients who had atrial fibrillation also had pacemakers. All males over 30 years of age had at least one of the following manifestations: cardiac hypertrophy, stroke, or proteinuria. In females, the severity of Fabry disease varied from classic multiorgan disease to a condition that mimicked the attenuated cardiac variant. No one was totally asymptomatic without any signs of Fabry disease. Cardiac magnetic resonance imaging was performed on nine of 14 patients was the most sensitive for detecting early cardiac manifestations. Five patients (55%) had late gadolinium enhancement‐positive segments.
Conclusion
Cardiac involvement should be effectively detected in females before considering them asymptomatic mutation carriers.